Optimalisasi Ekonomi Lokal Desa Paji Melalui Pengembangan Kompetensi Wirausaha Muda Karang Taruna dalam Pemanfaatan E-Commerce dan Platform Media Sosial - Margareta, Andini Ardy; Hamid, Ahmad Munir; A’ini, Huril (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2025)
This community service program was implemented to address the low level of digital marketing skills among young entrepreneurs of Karang Taruna in Paji Village, which has hindered the optimal development of local business potential. The program focuses on strengthening participants’ abilities in utilizing electronic commerce and social media as platforms for promoting village products. The purpose of this program is to improve participants’ skills in creating online stores, applying product image-building strategies, and developing digital content-based promotion. The approach used includes basic training on digital marketing concepts, direct assistance to ensure the practical application of skills in managing online marketing accounts, and evaluation of program outcomes. The program resulted in improved participant capabilities in creating online stores, producing promotional content, and establishing community-based marketing networks. The impact of the activities is reflected in the expanded marketing reach and strengthened identity of local products, although several challenges such as differences in technological proficiency and limited internet access were still encountered.